TOLERANSI ANTAR UMAT BERAGAMA UNTUK MEWUJUDKAN MODERASI ISLAM - Ash-Shiddiqy, Muhammad (Jurnal Dakwah Tabligh, 2021)
This research uses a qualitative approach. Sources of data obtained from primary data and secondary data. Data analysis using the descriptive phenomenological analysis method aims to describe the phenomenon of Islamic moderation with inter-religious tolerance. The results of the study are Islamic moderation with tolerance between religious communities, namely the progress of Islamic civilization. Muslims have a high tolerance for the progress of civilization and harmony. The occurrence of inter-religious tolerance cannot be separated from supporting and hindering factors. The supporting factors are religious teachings, the role of religious leaders, the role of the local government, the basic attitude of the local community, the attitude of ta’aruf (knowing each other), the attitude of tafahum (the attitude of understanding or understanding each other), the attitude of ta’awun (helping each other), history, economic activities, and the teachings of the ancestors. The inhibiting factors for tolerance are stereotypes, mutual suspicion, shallow religious knowledge, lack of understanding of the importance of living in harmony in society, mapping of places of residence, contempt for other groups, the majority and minority of the terms, and dislike of other people’s religious ways. forms of tolerance; mutual respect for different beliefs, mutual assistance, and cooperation in the success of existing religious events.